2014
DOI: 10.1074/jbc.m113.513879
|View full text |Cite
|
Sign up to set email alerts
|

The Diarylheptanoid Hirsutenone Sensitizes Chemoresistant Ovarian Cancer Cells to Cisplatin via Modulation of Apoptosis-inducing Factor and X-linked Inhibitor of Apoptosis

Abstract: Background: Resistance of ovarian cancer cells to chemotherapy is a major therapeutic problem.Results: Hirsutenone induces cisplatin sensitivity via p53, X-linked inhibitor of apoptosis protein, and apoptosis-inducing factor.Conclusion: Hirsutenone sensitizes resistant ovarian cancer cells to cisplatin.Significance: Co-treatment with hirsutenone may have the potential to overcome chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Diarylheptanoids are notable in the biomedical literature for their toxicity (Sati et al 2011) and promise for cancer treatments (Farrand et al 2014); some evidence also suggests diarylheptanoids inhibit digestion in herbivores (Sunnerheim and Bratt 2004). Diarylheptanoids are notable in the biomedical literature for their toxicity (Sati et al 2011) and promise for cancer treatments (Farrand et al 2014); some evidence also suggests diarylheptanoids inhibit digestion in herbivores (Sunnerheim and Bratt 2004).…”
mentioning
confidence: 99%
“…Diarylheptanoids are notable in the biomedical literature for their toxicity (Sati et al 2011) and promise for cancer treatments (Farrand et al 2014); some evidence also suggests diarylheptanoids inhibit digestion in herbivores (Sunnerheim and Bratt 2004). Diarylheptanoids are notable in the biomedical literature for their toxicity (Sati et al 2011) and promise for cancer treatments (Farrand et al 2014); some evidence also suggests diarylheptanoids inhibit digestion in herbivores (Sunnerheim and Bratt 2004).…”
mentioning
confidence: 99%
“…In particular, the anti‐adipogenic activity of phytochemicals that inhibit PI3K activation have been widely investigated. HST is a highly potent inhibitor of PI3K kinase activity in vitro [Farrand et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In chemo- and radiotherapy, similar signaling cascades are involved in the p53 activation of DNA damage, and the WT p53 gene plays an essential role in inducing apoptosis. It has been demonstrated that there were relevancies between the mutant p53 genes and resistance to chemotherapy in ovarian cancer [52], gastric and colorectal cancers [53], and in hematological malignancies [54]. In addition, dramatic differences were shown, indicating that the p53 status in tumors was not related to the chemotherapy response, but rather, that mutations in L2/L3 domains of the p53 gene in breast cancer were related to chemo-resistance [55].…”
Section: Clinical Issues and Experiences Of Gene Therapymentioning
confidence: 99%